Lateral transport on cell membranes: mobility of concanavalin A receptors on myoblasts. - Schlessinger, J (1976)
We report measurements of the lateral mobility of fluorescent labeled concanavalin A receptor complexes on the plasma membrane of cultured myoblasts of rat. Transport rates were measured by observing the recovery of fluorescence in a small region of the cell surface initially photobleached irreversibly by an intense, focused laser light pulse. Under different conditions we measured effective diffusion coefficients of the receptor complexes in the range 8 x 10(-12) less than D less than 3 x 10(-11) cm2/sec which is two orders of magnitude lower than we found for a fluorescent lipid probe, D approximately (8 +/- 3) x 10(-9) cm2/sec. This large difference and the presence of apparently immobile concanavalin A receptors suggests that factors beyond the fluoidity of the phospholipid bilayer membrane matrix control the rate of lateral transport of the complexes. Effective mobilities of the complexes decrease with increases in the valence, dose, and occupation time of the lectin on the membrane. These properties imply an aggregation of the lectin-receptor complexes. Mobilities are not influenced by azide, colchicine or preincubation at low temperature. Cytochalasin B and low temperatures, during the time of measurement, decrease the lateral transport rate.